1978
DOI: 10.1002/cpt1978233329
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride bioavailability after intravenous and oral administration: Importance of renal clearance and urine flow

Abstract: Fluoride (3 mg) was administered as a continous intravenous infusion during 30 min to 6 healthy subjects. Plasma concentrations and urinary excretion of fluoride in these experiments were compared with those obtained following oral administration of 2.82 mg, 4.50 mg, 5.64 mg, and 9.40 mg in the form of tablets and capsules. There were large day-to-day variations in the renal clearance of fluoride. This was shown to be due to differences in the urinary flow, an increase in flow causing an increase in renal clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(70 citation statements)
references
References 4 publications
8
62
0
Order By: Relevance
“…22 It was also of interest that the experiment showed that there was no rapid dissolution of the glass in the acidic environment of the stomach. The plasma peak levels achieved and the timing of the peak after ingestion of the NaF tablet are very similar to those reported by Trautner and Einwag 23 and also of Ekstrand et al 24 This was also shown in the animal experiments carried out by Mirth et al 5 with the copolymer membrane slow F releasing device, where there was no change in blood plasma F and no signs of toxicity. The conclusion to be drawn from this initial study was that should a glass pellet break or fall off its intra-oral site and was swallowed, there was no danger of the F being absorbed into the blood stream.…”
Section: Discussionsupporting
confidence: 87%
“…22 It was also of interest that the experiment showed that there was no rapid dissolution of the glass in the acidic environment of the stomach. The plasma peak levels achieved and the timing of the peak after ingestion of the NaF tablet are very similar to those reported by Trautner and Einwag 23 and also of Ekstrand et al 24 This was also shown in the animal experiments carried out by Mirth et al 5 with the copolymer membrane slow F releasing device, where there was no change in blood plasma F and no signs of toxicity. The conclusion to be drawn from this initial study was that should a glass pellet break or fall off its intra-oral site and was swallowed, there was no danger of the F being absorbed into the blood stream.…”
Section: Discussionsupporting
confidence: 87%
“…Renal clearance of fluoride showed large day-to-day variations depending on renal flow but extra renal clearance representing mainly clearance to bone pool and the fraction of intake remaining in pool bone pool showed remarkable consistency. In a subsequent study, the renal clearance of fluoride has been reported to be always lower with acid urine than with alkaline urine (Ekstrand et al, 1978(Ekstrand et al, , 1980. The extra-renal clearance of fluoride to the bone pool of fluoride was also found to be significantly lower during the production of alkaline urine.…”
Section: Discussionmentioning
confidence: 83%
“…Net fractional renal clearance decreased significantly ( r = Although plasma concentrations of fluoride, renal clcarance of fluoride, and fluoride pharmacokinetics have been extensively studied in human adults (27)(28)(29)(30)(31)(32)(33) and renal clearance of fluoride has been studied in children and adolescents (34). the data reported here arc the first concerning infants.…”
Section: Resultsmentioning
confidence: 99%
“…the area under the plasma concentration curve in a specified subject was greater when the fluoride dose was greater, but between subjects at the same fluoride intake. there was considerable variability in the area under the plasma concentration curve (27,28).…”
Section: Resultsmentioning
confidence: 99%